Improving cross-sector collaborations in place-based population health projects - Kenneth Lo; Craig Lockwood (Elsevier, 2022)
Objectives: The objective of this study is to develop a practice-orientated partnership framework that can enable effective population health collaborations in rural areas, and to gain ground insights on the role and policies of the Department of Families, Fairness and Housing (DFFH) in administering population health projects. Study design: Rapid evidence review and case study interviews with stakeholders. Methods: The framework development started with a rapid review to identify evidence-based practices on collaboration for population health stakeholders. Best-practices from DFFH's policy document for place-based projects were also incorporated into the framework. After a preliminary draft of the framework was ready, semi-structured interviews were conducted with stakeholders to seek practitioner insights to validate the framework and contextualise it to local needs. Results: Inputs from the stakeholder interviews were organised into two categories: "Inputs for framework" which contained responses that improved the framework, and "inputs for DFFH" which contained insights on the role and policies of DFFH in administering population health projects. Conclusions: With its list of actionable activities and enablers organised into logical project phases, the framework provides a practical and intuitive guide that can help stakeholders navigate through complex place-based population health projects. The inputs for DFFH provided the department with valuable ground insights into the dynamics of cross-sector collaborations for further reflection about their roles and policies. Through the consultative interview process which meaningfully engaged key stakeholders, a level of understanding and support for the framework was gained, which would encourage future implementations of place-based population health projects.